Effect of topical vapocoolant spray on perioperative pain response of unweaned calves to ear tagging and ear notching. (January 2017) - Lomax, Sabrina; Witenden, Emily; Windsor, Peter; White, Peter
Abstract: Objective: To evaluate the efficacy of a vapocoolant spray to provide local anaesthesia for calves during ear tagging and ear notching. Study design: Randomized study. Animals: Twenty Black Angus calves aged 4–16 weeks old. Methods: Temperature validation studies using thermocouples and a temperature data logger were conducted on dead and live tissue to determine optimal spray distance and duration to achieve tissue anaesthesia (<10 °C). A behavioural trial was conducted to assess efficacy for ear tagging and ear notching. Calves (n = 20) were randomly assigned to the vapocoolant spray (VS) or the water spray (WS) group. A 3 second spray was administered from 10 cm to both sides of the ear immediately prior to ear tagging and ear notching. A numerical rating scale (NRS) was used to score behavioural response to each procedure, with responses categorized from 0 (no response) to 3 (severe). Results: Temperature and tissue validation studies indicated that a vapocoolant spray reduced dead and live tissue temperature to below nociceptive threshold levels (10 °C) for 10–16 seconds. Univariate analysis indicated that ear notching was more painful than ear tagging [odds ratio (OR) = 19.2, 95% confidence interval (CI): 5.34–68.99, p < 0.001]. When adjusted for the multivariate model, there was a significant effect of treatment, with WS calves showing higher pain response scores than VS calves (OR = 4.08, 95% CI: 1.34–12.42, p  = 0.011). Ear notching resulted in greater pain response scores than ear tagging (OR = 23.19, 95% CI: 6.18–87.05, p < 0.001). Conclusions: and clinical relevance Vapocoolant spray induced local anaesthesia and significantly reduced the pain response to ear tagging and ear notching in calves. Ear notching is more painful than ear tagging. Cryoanaesthesia is an effective option for reducing the perioperative pain associated with these simple husbandry procedures.